Primary hypertrophic osteoarthropathy presenting as juvenile idiopathic arthritis: a case report - Samuel, Merwin; Rajamurugan, Arul; Subramanian, Ramesh; Ramamoorthy, Ramesh (International Journal of Contemporary Pediatrics, 2025)
Primary hypertrophic osteoarthropathy (PHO) is an inherited disorder, characterised by skin thickening of face and extremities, and periosteal proliferation of the long bones. It is caused by HPGD or SLCO2A1 gene mutations, inherited in an autosomal dominant or recessive pattern. It presents with characteristic skin changes and musculoskeletal pain. We present the case of an adolescent male patient with hypertrophic osteoarthropathy. We managed him successfully with zolendronic acid.